Properties of Host Galaxies of Submillimeter Sources as Revealed by JWST Early Release Observations in SMACS J0723.3–7327 - Cheng, Cheng; Yan, Haojing; Huang, Jia-Sheng; Willmer, Christopher N. A.; Ma, Zhiyuan; Orellana-González, Gustavo (Astrophysical journal. Letters, 2022)
Using the 0.9–4.4 μ m imaging data from the James Webb Space Telescope (JWST) early release observation in the SMACS J0723.3–7327 galaxy cluster field, we discuss the properties of three submillimeter galaxies (SMGs) detected by the Atacama Large Millimeter/submillimeter Array Array. These sources are magnified by 1.4–2.1 × due to gravitational lensing. This is the first time that submillimeter galaxy hosts are resolved in the rest-frame near-infrared (NIR). One source was previously undetected by Hubble Space Telescope, while the remaining two are disk galaxies with Sérsic indices of ∼0.9 and star formation rates on or just below the star formation “main sequence.” Their submillimeter emission originates from the inner parts of the hosts, suggesting that their dust contents are concentrated toward the center. The host half-light radii measured in the rest-frame NIR are ∼1.5 × smaller than those measured in the rest-frame optical, consistent with a concentrated dust distribution. The more severe extinction that optical light suffers toward the center makes it seemingly less concentrated. Therefore, we expect that the optically based determination of the stellar mass distribution within host galaxies could still be severely biased by dust. Interestingly, these two disk galaxies are dramatically different in their outer regions, with one being star forming and the other being quiescent. Upcoming JWST observations of statistically significant samples of SMGs will allow us to understand the correlation between the dusty star-forming regions and their hosts.